Bitterness and astringency of tea leaves and products: Formation mechanism and reducing strategies. (May 2022) - Ye, Jian-Hui; Ye, Ying; Yin, Jun-Feng; Jin, Jing; Liang, Yue-Rong; Liu, Ru-Yi; Tang, Ping; Xu, Yong-Quan
Abstract: Background: The bitter and astringent taste of tea and tea extract is still not favored by many consumers, which limits its applications to bakery foods and functional foods. Many bitter and astringent compounds in tea leaves are susceptible, which transform during tea processing or can be modified by food production technologies. Besides, the accumulations of the major bitter and astringent compounds in fresh tea leaves, such as alkaloids and flavonoids, can be regulated by agronomic practices. Many attempts have been made to reduce the bitter and astringent compounds, in order to improve the sensory quality of tea and tea products. Scope and approach: The aim of this review is to describe the characteristics of major bitter and astringent compounds in different types of teas as well as the bitterness and astringency reducing strategies from the aspects of preharvest, processing and post-processing. Key findings and conclusions: Alkaloids, catechins, anthocyanins, phenolic acids, flavonol glycosides, and theaflavins importantly contribute to the bitter and astringent taste of tea infusion, the contents of which can be modulated during preharvest, processing, and post-processing. Shade treatment is a conventional agronomic practice to reduce the bitterness and astringency of tea. Processing methods like oxidation, roasting/baking and microbial fermentation effectively reduce the bitter and astringent intensities of teas, but have restricted applications to special types of tea. There is a need of new compounds or strategies to decrease the bitterness and astringency of tea and tea products. Employment of these bitterness and astringency reducing strategies should consider the appearance or application requirements of final products. Highlights: Tea taste can be modulated from preharvest, processing, and post-processing. Shade treatment is an agronomic practice to reduce bitterness and astringency. PPO-induced enzymatic reaction reduces the bitterness and astringency of tea. Bitter and astringent flavonoids are susceptible to high temperature. Microbes transform alkaloids and flavonoids to reduce bitterness and astringency.